Reconstructing the evolution of ice sheets, sea level, and atmospheric CO 2 during the past 3.6 million years - Berends, Constantijn J.; De Boer, Bas; Van De Wal, Roderik S.W. (Climate of the Past, 2021)
Understanding the evolution of, and the interactions between, ice sheets and the global climate over geological timescales is important for being able to project their future evolution. However, direct observational evidence of past CO2 concentrations, and the implied radiative forcing, only exists for the past 800 000 years. Records of benthic δ18O date back millions of years but contain signals from both land ice volume and ocean temperature. In recent years, inverse forward modelling has been developed as a method to disentangle these two signals, resulting in mutually consistent reconstructions of ice volume, temperature, and CO2. We use this approach to force a hybrid ice-sheet climate model with a benthic δ18O stack, reconstructing the evolution of the ice sheets, global mean sea level, and atmospheric CO2 during the late Pliocene and the Pleistocene, from 3.6 million years (Myr) ago to the present day. During the warmerthan-present climates of the late Pliocene, reconstructed CO2 varies widely, from 320 440 ppmv for warm periods to 235 250 ppmv for the early glacial excursion ∼ 3:3 million years ago. Sea level is relatively stable during this period, with maxima of 6 14 m and minima of 12 26 m during glacial episodes. Both CO2 and sea level are within the wide ranges of values covered by available proxy data for this period. Our results for the Pleistocene agree well with the ice-core CO2 record, as well as with different available sea-level proxy data. For the Early Pleistocene, 2.6 1.2 Myr ago, we simulate 40 kyr glacial cycles, with interglacial CO2 decreasing from 280 300 ppmv at the beginning of the Pleistocene to 250 280 ppmv just before the Mid-Pleistocene Transition (MPT). Peak glacial CO2 decreases from 220 250 to 205 225 ppmv during this period. After the MPT, when the glacial cycles change from 40 to 80 120 kyr cyclicity, the glacial interglacial contrast increases, with interglacial CO2 varying between 250 320 ppmv and peak glacial values decreasing to 170 210 ppmv.